Example-Based Moral Education in Abdullah Nashih Ulwan’s Thought and Its Contemporary Relevance - Muharor, Mohammad Zaki; Ratna, Afenda; Shidqi, Ahmad Fakhris; Ikmal, Hepi (Peradaban Journal of Interdisciplinary Educational Research, 2025)
This study examines the thought of Abdullah Nashih Ulwan on moral education through the method of exemplification (role modeling). In the midst of increasing moral decline in contemporary society, Ulwan’s approach offers an Islamic pedagogical model that emphasizes character formation through lived examples rather than mere verbal instruction. Employing a qualitative library research method, this study analyzes Ulwan’s seminal work Tarbiyatul Aulad fil Islam along with supporting literature and modern educational theories. The findings reveal three core principles of Ulwan’s concept of moral education: consistency between words and actions, sincerity of intention, and the embodiment of Islamic values in daily life. His perspective resonates with Bandura’s social learning theory, which highlights the role of social environment and behavioral modeling in shaping character. The study concludes that Ulwan’s ideas remain relevant in addressing the moral challenges of today’s youth and provide practical implications for families, schools, and educational policy. These findings reaffirm the central role of educators as moral exemplars and emphasize the need for a holistic integration of ethical conduct into all dimensions of the educational process. Penelitian ini mengkaji pemikiran Abdullah Nashih Ulwan tentang pendidikan moral melalui metode keteladanan (role modeling). Di tengah meningkatnya gejala dekadensi moral pada era kontemporer, pendekatan Ulwan menawarkan model pedagogis Islam yang menekankan pembentukan akhlak melalui contoh nyata, bukan sekadar instruksi verbal. Penelitian ini menggunakan metode kualitatif studi pustaka dengan menelaah karya utama Ulwan Tarbiyatul Aulad fil Islam serta literatur pendukung dan teori pendidikan modern. Hasil kajian menunjukkan bahwa Ulwan menekankan tiga prinsip utama pendidikan moral: konsistensi antara ucapan dan perbuatan, ketulusan niat, serta penghayatan nilai-nilai Islam dalam kehidupan sehari-hari. Perspektif ini selaras dengan teori pembelajaran sosial Bandura yang menekankan peran lingkungan sosial dan peniruan perilaku dalam pembentukan karakter. Penelitian ini menyimpulkan bahwa pemikiran Ulwan tetap relevan dalam menjawab tantangan moral generasi muda dan memberikan kontribusi praktis bagi keluarga, sekolah, dan kebijakan pendidikan. Temuan ini menegaskan pentingnya peran pendidik sebagai teladan moral serta perlunya integrasi holistik etika ke dalam seluruh dimensi pengalaman pendidikan.